Memoirism hype - Udovič, Boštjan (Acta neophilologica, 2020)
Literary theory puts memoirs on the intersection between literary and semi-literary gen-res, which makes them specific by definition. But when we talk about memoirs of dip-lomats, they are even more specific, as they are often the only source describing events that took place in diplomatic intercourse. This article analyses the significance of writing memoirs as seen by diplomats through interviews with ten Slovenian diplomats. The in-terviewees agree that memoirs need to be written, not only to shed light on events that took place in diplomacy, but also because they can be important literary works and con-tribute to the spread of diplomatic terminology
Keywords: Diplomacija; Diplomacy; Diplomati; Diplomats; memoari; memoirs; pisanje spominov; politicians; politiki; Slovene diplomats; Slovene politicians; slovenski diplomati; spomini